Membrane lipid microenvironment modulates thermodynamic properties of the Na+-K+-ATPase in branchial and intestinal epithelia in euryhaline fish in vivo - Diaz, Mario; Dopido, Rosa; Gomez, Tomas; Rodriguez, Covadonga (Frontiers in Physiology, 2016)
We have analyzed the effects of different native membrane lipid composition on the thermodynamic properties of the Na+-K+-ATPase in different epithelia from the gilthead seabream Sparus aurata. Thermodynamic parameters of activation for the Na+-K+-ATPase, as well as contents of lipid classes and fatty acids from polar lipids were determined for gill epithelia and enterocytes isolated from pyloric caeca, anterior intestine and posterior intestine. Arrhenius analyses of control animals revealed differences in thermal discontinuity values (Td) and activation energies determined at both sides of Td between intestinal and gill epithelia. Eyring plots disclosed important differences in enthalpy of activation (H‡) and entropy of activation (S‡) between enterocytes and branchial cells. Induction of n-3 LCPUFA deficiency dramatically altered membrane lipid composition in enterocytes, being the most dramatic changes the increase in 18:1n-9 (oleic acid) and the reduction of n-3 LCPUFA (mainly DHA, docosahexaenoic acid). Strikingly, branchial cells were much more resistant to diet-induced lipid alterations than enterocytes, indicating the existence of potent lipostatic mechanisms preserving membrane lipid matrix in gill epithelia. Paralleling lipid alterations, values of Ea1, H‡ and S‡ for the Na+-K+-ATPase were all increased, while Td values vanished, in LCPUFA deficient enterocytes. In turn, Differences in thermodynamic parameters were highly correlated with specific changes in fatty acids, but not with individual lipid classes including cholesterol in vivo. Thus, Td was positively related to 18:1n-9 and negatively to DHA. Td, Ea1 and H‡ were exponentially related to DHA/18:1n-9 ratio. The exponential nature of these relationships highlights the strong impact of subtle changes in the contents of oleic acid and DHA in setting the thermodynamic properties of epithelial Na+-K+-ATPase in vivo. The effects are consistent with physical effects on the lipid membrane surrounding the enzyme as well as with direct interactions with the Na+-K+-ATPase.